FISH HATCHERY INCOME ANALYSIS IN THE INGIN MAJU GROUP MUNGO REGION LUAK SUB-DISTRICK LIMA PULUH KOTA DISTRICK WEST SUMATERA PROVINCE - Surya, Jaka; Arief, Hazmi; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Ingin Maju group is one fishery grouplocated in Mungo Region, Luak Subdistrick, Lima Puluh Kota Districk, West Sumatera Province, which consistenly develops fisheries sector, especially freshwater fish hatchery business. Currently, there are four types of fish hatchery business that is developed in the Ingin Maju group, which are the fish hatchery business Gurami fish, Lele fish, Nila fish and Mas fish. The research aims to analyze the fish hatchery business in Ingin Maju group, included : type of fish hatchery that is most profitable, business feasibility and productivity. Data were collected by survey method from 7 fish farm in Ingin Maju group and its data is processed using income anlysis, feasibility and productivity.The result of the research showed that Gurami, Lele and Nila fish hatchery bussines is the most profitable with the net income of Rp 5.385.700/year. Furthermore, using the business feasibility resulted the average of Revenue Cost of Ratio got by fish hatchery business in Ingin Maju group is 2,09, the average of Financial Rate of Return is 266% and the average of Payback Period of Capital is 0,38. Productivity of fish hatchery business in Ingin Maju group is 606 fish/m2.Keywords : Fish Hatchery Income, Ingin Maju Group